National Cancer Institute, Putrajaya - Muhammad Nur, Muhammad Aqil; Zamri, Muhammad Danish Daniel; Hanafi, Syazrina (2024)
In 2003, the Ministry of Health (MOH) reported that cancer accounted for 9.34% of all deaths in Malaysia compared to 7.37% in 1975. The findings in the First Report of the National Cancer Registrar are estimated that the risk of developing cancer in Malaysia is 1 in 4. In this regard, the establishment of the National Cancer Institute (NCI) is expected to meet the needs of cancer patients in Malaysia. The construction project of the National Cancer Institute is a long-awaited project, and it is the government's social responsibility to provide world-class health care in meeting the aspirations of the 2020 vision towards making Malaysia a developed nation. The National Cancer Institute is a cancer medical institution specially built to provide specialized medical facilities in the treatment and medicine of cancer patients. The establishment of the National Cancer Institute is aimed at addressing the growing needs related to cancer issues in the country.